Detection and genetic characterisation of porcine circovirus 3 from pigs in Sweden - Ye, Xingyu; Berg, Mikael; Fossum, Caroline; Wallgren, Per; Blomström, Anne-Lie (Virus genes, 2018)
Porcine circovirus 3 (PCV3) is a newly detected circovirus belonging to the family Circoviridae with a circular ssDNA genome of 2000 bp that encodes two proteins—the replicase protein and the capsid protein. PCV3 was discovered for the first time in the US in 2016. After this initial discovery, PCV3 was detected in other parts of the world such as in China, South Korea, Italy and Poland. In this study, 49 tissue samples from Swedish pig herds were screened for PCV3 using PCR and 10 samples were positive and one was uncertain. The entire PCV3 genome and a mini PCV-like virus (MPCLV) were obtained from one of these samples. These two viruses showed a high sequence identity to PCV3 viruses from other countries as well as to MPCLV from the US. However, the sequence identity to PCV1 and 2 was only 31–48% on amino acid level. This is the first detection and complete genetic characterisation of PCV3 in Swedish pigs. It is also interesting to note that one of the positive samples was collected in 1993, showing that PCV3 has been present for a long time.